Atheroprotective Mechanisms of Tilianin by Inhibiting Inflammation Through Down-Regulating NF-κB Pathway and Foam Cells Formation - Shen, Wanli; Anwaier, Gulinigaer; Cao, Yini; Lian, Guan; Chen, Cong; Liu, Shu; Tuerdi, Nuerbiye; Qi, Rong (Frontiers in Physiology, 2019)
Tilianin, a representive flavonoid ingredient of Dracocephalum Moldavia L, has been used to treat several diseases for centuries, including atherosclerosis (AS). However, pharmacological mechanisms underlying its biological functions remain elusive. In the present study, we investigated the anti-AS mechanisms of tilianin through establishing in vitro models using three types of cells that contributed to AS progression, including macrophage, vascular smooth muscle cells and human umbilical vein endothelial cells, which were proved to be involve in LPS/TNF-α/ox-LDL-induced inflammation and ox-LDL induced foam cell formation. Our results indicate that tilianin significantly suppressed LPS induced inflammatory responses on macrophage and remarkably inhibited TNF-α induced VSMCs proliferation and migration. Furthermore, the anti-inflammatory effect of tilianin on macrophages and VSMCs was proved to be mainly by downregulating TNF-α/NF-κB pathway. Moreover, our results demonstrate that tilianin significantly ameliorated ox-LDL induced macrophages oriented foam cells formation through repressing mRNA expression of SR-A1 and inducting the expression of genes related to cholesterol efflux including SRB-1and ABCA1. However, tilianin had no effect on ox-LDL induced HUVECs injury.